Overall survival of patients with CLL treated with ibrutinib in the first line compared to second-line ibrutinib after chemotherapy/chemoimmunotherapy - Robak, Tadeusz; Doubek, Michael; Ferrant, Emmanuelle; Diels, Joris; Andersone, Liva; Wilbertz, Sabine; Healy, Nollaig C; Neumayr, Lynne; van Sanden, Suzy (Current medical research and opinion, 2024)
OBJECTIVE: To evaluate the overall survival (OS) of patients with chronic lymphocytic leukemia (CLL) receiving either ibrutinib monotherapy as a first-line (1L) treatment or chemotherapy/chemoimmunotherapy-based (CT/CIT) regimens in 1L followed by ibrutinib in the second line (1L CT/CIT-2L ibrutinib) after disease progression by emulating a randomized trial comparing both treatment sequences. METHODS: Patient-level data from the RESONATE-2 trial (NCT01722487) and real-world PHEDRA databases were analyzed. Three scenarios were considered using the following data sources: (1) RESONATE-2, (2) combined RESONATE-2/PHEDRA, (3) combined RESONATE-2/PHEDRA for 1L ibrutinib and PHEDRA for 1L CT/CIT-2L ibrutinib. Propensity score-based weights and inverse probability of censoring weighting were used to adjust for baseline (Scenarios 2 and 3) and time-dependent confounding (all scenarios), and to address potential biases. A weighted Cox proportional hazards model was used to estimate the OS hazard ratio (HR) and 95% confidence interval (CI) for 1L ibrutinib versus 1L CT/CIT-2L ibrutinib. RESULTS: Results from Scenario 1 showed a significantly lower risk of death with 1L ibrutinib compared with 1L chlorambucil followed by 2L ibrutinib (HR 0.35 [95% CI 0.20-0.62]). Results from Scenarios 2 and 3 demonstrated a reduced risk of death with 1L ibrutinib compared with 1L CT/CIT-2L ibrutinib (HR 0.35 [0.21-0.61] and 0.64 [0.39-1.04], respectively). CONCLUSION: The analyses consistently showed a reduced risk of death when ibrutinib was used as a 1L treatment in CLL compared with delaying its use until 2L after CT/CIT regimens, which suggests that initiating ibrutinib in 1L is advantageous for improving survival outcomes.
Keywords: pyrazoly; Adenine; Humans; lidé středního věku; pyrimidiny; Female; Aged; protokoly protinádorové kombinované chemoterapie; senioři; lidé; Immunotherapy; chronická lymfatická leukemie; Piperidines; Leukemia, Lymphocytic, Chronic, B-Cell; adenin; ženské pohlaví; Male; Middle Aged; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; senioři nad 80 let; piperidiny; míra přežití; Pyrimidines; mužské pohlaví; Pyrazoles; imunoterapie; Survival Rate